Proceedings of the 21st International Conference on Evaluation and Assessment in Software Engineering 2017
DOI: 10.1145/3084226.3084265
|View full text |Cite
|
Sign up to set email alerts
|

What Do We Know about Alignment of Requirements Engineering and Software Testing?

Abstract: Context:The alignment of different software engineering activities for coordinated functioning and optimized product development is of great importance, particularly in industrialscale development. The link between intermediate activities has been researched extensively, but the link between requirements engineering (RE) and software testing (ST) is a relatively less explored area. Objective: The objective of this study is to aggregate, structure, and classify all existing research regarding alignment of RE an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In cases of large systems with complex dependencies in which some level of hierarchy is need for decision making, there is an increased general need to pay careful attention to aspects such as documentation, communication, and traceability, as well as to generally and carefully align RE with testing through people, processes, and artifacts. This alignment has been the interest of many large software development organizations in the automotive and avionic domains (Karhapää et al 2017), and QR management could benefit from it.…”
Section: Ec6mentioning
confidence: 99%
“…In cases of large systems with complex dependencies in which some level of hierarchy is need for decision making, there is an increased general need to pay careful attention to aspects such as documentation, communication, and traceability, as well as to generally and carefully align RE with testing through people, processes, and artifacts. This alignment has been the interest of many large software development organizations in the automotive and avionic domains (Karhapää et al 2017), and QR management could benefit from it.…”
Section: Ec6mentioning
confidence: 99%
“…The second session started with an invited talk on a systematic mapping study that reviewed the scientific literature addressing requirements engineering and software testing alignment. Karhapää presented his work, previously published at the 21st Conference on Evaluation and Assessment in Software Engineering (EASE 2017) [4], in which the authors identified 7 focus areas in the 80 reviewed publications. Prior to the workshop, we used their structure to create a visual map of research on RET alignment, including their assessments of rigor and relevance [3].…”
Section: B Sessionmentioning
confidence: 99%